A polyamidoamne dendrimer functionalized graphene oxide for DOX and MMP-9 shRNA plasmid co-delivery - Gu, Y.; Guo, Y.; Wang, C.; Xu, J.; Wu, Jian-Ping; Kirk, T.; Ma, D.; Xue, W. (Elsevier, 2017)
© 2016 Elsevier B.V. It is a promising way to treat the multi drug resistance (MDR) of tumor cells in both of drug and gene methods. A polyamidoamne dendrimer functionalized graphene oxide (GO-PAMAM) was designed, which could load doxorubicin (DOX) and MMP-9 shRNA plasmid at the same time in order to achieve effective treatment to breast cancer. GO-PAMAM has a high loading capacity to DOX and pH-controlled DOX release. Besides, it has efficient gene transfer ability, the transfection efficiency is significantly better than PEI-25k in the presence of serum, and it can significantly inhibit the expression of MMP-9 protein in MCF-7 cells. The effect of DOX and MMP-9 shRNA plasmid co-delivery was more significant than that of the single drug. Moreover, GO-PAMAM exhibited lower cytotoxicity compared to PEI-25k in CCK-8 assays, and also showed a good biocompatibility in vivo. Therefore, GO-PAMAM will have broad prospects for drug and gene co-delivery.